Context-Driven Entrepreneurial Education in Vocational Schools - Sandirasegarane, Sharmila; Sutermaster, Staci; Gill, Alyssa; Volz, Jennifer; Mehta, Khanjan (International Journal for Research in Vocational Education and Training, 2016)
Vocational Education and Training (VET) is offered throughout the world to students of various educational backgrounds and career aspirations in an effort to create a skilled workforce. The structure of VET varies greatly across different fields and countries with high-growth, low-growth, and transitional economies. However, a common critique of many vocational institutions is that they focus on skills training without addressing related business systems. Thus, students may not understand the business strategies related to their field, which stifles job readiness and entrepreneurial potential. To counter this, a more context-driven and integrated entrepreneurial approach is proposed for VET. Benefits, disadvantages, and exemplars of various types of vocational and entrepreneurial programs are evaluated to determine how their strengths might be leveraged. Such integrated entrepreneurial and vocational training would more suitably address context-specific market needs via both practical and transferrable skills, thus helping to reduce unemployment, particularly among youth in sub-Saharan Africa.